The Role of Women to Program Agribusiness Driving in Air Talas Tourism Village (ANGGREK DEWATA) - Catherine Wahyuning Wilujeng; Erwin Hendra Putra; Wawan Hendrawan; Willy Rochel; Azrah Andriani; Dwi Novanda Sari; Hengky Rosadi; Dewi Ratna Sari; Irfan Ripandi (Pelopor Publikasi Akademika, 2024)
This research method takes the form of a qualitative field study or field research. The data collection techniques were carried out using observation with active participation, in-depth interviews, documentation and focus group discussions. The research results show: In the Agribusiness Program Driving Talas Air Tourism Villages (ANGGREK DEWATA) there are 3 (three) programs carried out by PT Pertamina EP Limau Field, namely: BU JUSI (Organic Cultivation of Siamese Oranges), BUDE ARTA MAJU (Women of Air Talas Village Managing Oranges) and PUTERI JELITA (Liquid Fertilizer from Air Talas Orange Waste. The economic impact of this program for women is an increase in family income by IDR 2,500,000/person/month or 20% from the previous year from product sales. This program also has a positive social and environmental impact. This is in line with the fifth SDG goal, namely gender equality Talas (DEWATA ORGANGREK) from the Social Return on Investment (SROI) Report shows that the calculated SROI value of the program is 1.66, indicating that every rupiah of program costs produces a positive change worth IDR 1.66. Meanwhile, from the results of the Community Satisfaction Index assessment, the Anggrek Dewata Program obtained Community Satisfaction Index (IKM) results with the predicate